3D printing and morphological characterisation of polymeric composite scaffolds. (1st August 2020) - Oladapo, Bankole I.; Ismail, Sikiru O.; Zahedi, Mohsen; Khan, Affan; Usman, Hazrat
Highlights: Imitation of biomaterial composites used for bone implants, using gradual PLA/cHA bio-composites. Investigation of mechanical, chemical and physical properties of the biomaterials with three aggregates. Microstructural analysis of roughness and morphology of PLA/cHA scaffolds, using computerized micro-tomography technique. Assessment of the hybrid scaffolds: surface roughness evaluation, mechanical and bioactivity analysis tests. The compatibilised PLA/cHA morphological blends exhibited high toughness than pure PLA. Abstract: 3D-printing is an efficient method of designing customised structures and producing synthetic bone grafts appropriate for bone implants. This research aimed to manufacture a new multi-functionalised 3D-printed poly(lactic acid)/carbonated hydroxyapatite (PLA/cHA) scaffolds with mass proportions of 100/0, 95/5 and 90/10 in a bid to verify their potential application in tissue regeneration. The filaments of these hybrid materials were obtained by extrusion technique and subsequently used to manufacture the 3D-printed scaffolds, using a fused deposition modelling (FDM) technique. The scaffolds were characterised based on their thermal properties, microstructure and geometry by differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS), respectively, in addition to determination of their apparent porosities. The degradation of the scaffolds and the liberation of degradation products were evaluated in in vitro for different days under simulated physiological conditions. New microanalyses of mechanical behaviour of the materials: tensile and compression stresses, density, frequency analysis and optimisation with DSC were performed. While, evaluation of the surface luminance structure and the profile structure of the nanostructured PLA composite materials was done by SEM, in 3D printed form. The filter profile of cross-sectional view of the specimen was extracted and evaluated with Firestone curve of the Gaussian filter; checking the roughness and waviness profile of the structure. It was observed that the thermal properties of the composites were not affected by the manufacturing process. The microstructural analysis showed the effective incorporation of the ceramic filler in the polymer matrix as well as an acceptable PLA/cHA interaction. The degradation tests showed the presence of calcium and phosphorus in the studied medium, confirming their liberation from the composites during the incubation periods.